2018
DOI: 10.1063/1.5037482
|View full text |Cite
|
Sign up to set email alerts
|

Advances in milestoning. II. Calculating time-correlation functions from milestoning using stochastic path integrals

Abstract: In the milestoning framework, and more generally in related transition interface sampling schemes, one significantly enhances the calculation of relaxation rates for complex equilibrium kinetics from molecular dynamics simulations between the milestones or interfaces. The goal of the present paper is to advance milestoning applications into the realm of non-equilibrium statistical mechanics, in particular, to calculate entire time correlation functions. In order to accomplish this, we introduce a novel methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…So p 0 = (0, 1, 0, 0, 0). Recently Grazioli and Andricioaei have shown that time correlation functions can also be calculated by using the transition kernel and the first passage time distribution between milestones 75 . For that, a move from milestone i to j is proposed with probability p i→ j where…”
Section: A Milestoningmentioning
confidence: 99%
See 1 more Smart Citation
“…So p 0 = (0, 1, 0, 0, 0). Recently Grazioli and Andricioaei have shown that time correlation functions can also be calculated by using the transition kernel and the first passage time distribution between milestones 75 . For that, a move from milestone i to j is proposed with probability p i→ j where…”
Section: A Milestoningmentioning
confidence: 99%
“…Moreover, Grazioli and Andricioaei have developed an enhanced milestoning protocol by applying biasing force to obtain quick convergence for milestone to milestone trajectories 19 . They also have come up with a strategy to calculate time correlation functions from milestoning simulation using stochastic path integral 75 .…”
Section: Introductionmentioning
confidence: 99%
“…Developed independently about 16 years ago, the milestoning technique of Elber and coworkers 39 is another powerful method that can be used to compute timescales, as well as free energy profiles along suitably chosen directions in con-figuration space. In a recent work, the mathematical details of milestoning theory have been clarified 40 , allowing the calculation of many thermodynamic and kinetic properties including mean first passage times 41,42 , free energy profiles [43][44][45] , committor probabilities 46 , and time-correlation functions 47 .…”
Section: Introductionmentioning
confidence: 99%
“…In practice, previous milestoning calculations have been limited to calculating the constant flux values representative of the system at equilibrium, which can be thought of as the long time flux values lim t→∞ P s (t). A method for calculating the time-dependent flux through a given milestone P s (t) can be found in the companion paper to this article, also in this publication [13]. The aim of the technique we present in this paper is to increase the computational speed of the milestoning method via the addition of an artificial constant force (F wind ) along the vector pointing from the initial state to the final state for each pair of milestones in the simulation, causing the system to arrive at the destination configuration in far fewer time steps than if it were left to Brownian dynam-ics alone.…”
Section: Introductionmentioning
confidence: 99%